2020
DOI: 10.1002/jhbp.714
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of pancreatic juice reflux in pancreaticobiliary maljunction: A fluid dynamics model experiment

Abstract: Background Pancreatic juice reflux to the common bile duct and gallbladder is observed in the pancreaticobiliary maljunction (PBM), and various pathological conditions occur in the biliary tract. However, the mechanism of pancreatic juice reflux has not been discussed yet. This study aimed to investigate the mechanism of this phenomenon from the perspective of the fluid dynamics theory. Methods A fluid dynamics model of PBM without biliary dilatation having gallbladder function and of the pressure of sphincter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 7 publications
2
15
0
2
Order By: Relevance
“…This is the anatomic basis on which we postulate that some form of SO malfunction affecting one or all its components is the cause of the reflux of pancreatic enzymes. Recent experimental research by Fukuzawa 21 states that the pressure of the SO is constant and that pancreatic juice reflux is observed when the SO pressure is higher than the common bile duct pressure but not with lower pressure, additionally supporting our hypothesis. The human bile duct lacks a contractile muscle layer 8,9,20,22‐27 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is the anatomic basis on which we postulate that some form of SO malfunction affecting one or all its components is the cause of the reflux of pancreatic enzymes. Recent experimental research by Fukuzawa 21 states that the pressure of the SO is constant and that pancreatic juice reflux is observed when the SO pressure is higher than the common bile duct pressure but not with lower pressure, additionally supporting our hypothesis. The human bile duct lacks a contractile muscle layer 8,9,20,22‐27 .…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, it has been experimentally demonstrated that the contraction of the gallbladder releasing bile into the common bile duct also affects the intraductal pressure. 21 Normal sphincter activity directs the flow of bile and pancreatic juice towards the duodenum by antegrade phasic contractions. [28][29][30] Consequently, in patients with pancreatobiliary reflux with normal pancreatobiliary junction, the only plausible explanation for reflux of pancreatic juice into the biliary tract is an anomaly in the SO normal function causing a functional obstruction to the normal flow and retrograde contractions spasms the reflux of pancreatic juice into the biliary tract, because the intraluminal pressure of the pancreatic duct is higher than CBD intraluminal pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta es la base anatómica sobre la cual postulamos a la disfunción de uno o todos los componentes del EO como la causa del RPB. Recientemente, Fukuzawa publicó los resultados de un estudio experimental en el que demostró que la presión del EO es constante y que es posible observar RPB cuando la presión del EO se eleva significativamente sobre la presión de la VBE, este fenómeno no se observó con presiones bajas del EO 20 . El estudio de Fukuzawa constituye nueva evidencia que apoya nuestros resultados.…”
Section: Discussionunclassified
“…In patients with APBJ, pancreaticobiliary reflux often causes biliary cancer, biliopancreatic reflux often causes acute or chronic pancreatitis. Bile ducts DOI: 10.37990/medr.865798 of APBJ patients are considered premalignant and prophylactic surgery is recommended as soon as the diagnosis is made (7)(8)(9). In ERCP (endoscopic retrograde cholangiopancreotography), a long common duct, an abnormal bile-pancreatic duct junction and a contraction sphincter distal to the union are features of APBJ.…”
Section: Discussionmentioning
confidence: 99%